Web-Based Information Systems for Political Parties and Community Organizations Using Extreme-Programming Methods - Yassir, Muhammad; Gafur; Suhada, Sitti; Fitriati, Ita (Jurnal Teknik, 2023)
Badan Kesatuan Bangsa dan Politik is expected to be able to carry out its tasks and functions as a promoter of government affairs in the area of national unity and politics. However, there is still a frequent process of verification of registration files of association organizations and political parties, which is interrupted so that the registration process becomes obstructed. There are no available data on the existence and management of both social organizations and political parties. Delivery of accountability reports for political party funds is always late so the financial administration process is hampered, causing low budget absorption. Delivery of data desks of elections of heads of district or general elections is still manual, so late incoming reports cause information to the leadership to be unupdated. The research is aimed at building a web-based information system that provides registration, verification and filing features for political parties and association organizations. The method used is Extreme Programming with phases of planning, design, encoding, and testing. The results of this study resulted in a reliable and easy-to-use information system and showed 100% accuracy of the black box test results.